2011
DOI: 10.1017/s1368980010003769
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and socio-economic factors related to food intake and adherence to nutritional recommendations in a cohort of pre-school children

Abstract: Objective: To examine: (i) children's food intake and adherence to both Canada's Food Guide for Healthy Eating and Dietary Reference Intakes; and (ii) the social and demographic factors related to children's food intake. Design: A cross-sectional study. Setting: Data were obtained through the Quebec Longitudinal Study of Child Development 1998-2010, a representative sample (n 2103) of children born in 1998 in the province of Quebec, Canada. Information on energy, macronutrient and food consumption was derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
8
23
1
Order By: Relevance
“…Study results complement a recently published study reporting that moving from the highest income to the lowest income was associated with poorer variety of fruit consumption among 5-year-old children in Scotland 31. This study extends to middle childhood and early adolescence from Dubois et al 's previous findings of the QLSCD children at 4 years of age,16 which reported household income was significantly associated with fruit and vegetable consumption, but not with dairy consumption.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Study results complement a recently published study reporting that moving from the highest income to the lowest income was associated with poorer variety of fruit consumption among 5-year-old children in Scotland 31. This study extends to middle childhood and early adolescence from Dubois et al 's previous findings of the QLSCD children at 4 years of age,16 which reported household income was significantly associated with fruit and vegetable consumption, but not with dairy consumption.…”
Section: Discussionsupporting
confidence: 82%
“…Covariates in the multivariable analyses included demographic (such as age, sex), household (such as whether at least one parent had at least a high-school education at study enrolment, and whether the mother was an immigrant), and health characteristics (such as whether the child was overweight or obese) that have previously been shown to be associated with either poverty or nutritional behaviours 16 17. At each data collection wave, children's height and weight were measured in duplicate by trained study staff using a standard measuring tape to the nearest 0.1 cm, and a calibrated spring scale to the nearest 0.1 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings of the influence of maternal education or SEP were observed in studies assessing both meeting feeding guidelines (e.g. appropriate age of solids introduction) and child dietary patterns from the USA [91][92][93], Canada [94,95], UK [96,97], France [98], Australia [99], Brazil [100] and Peru [101]. A 2009 review of the determinants of early weaning and the introduction of cow's milk in infants found strong evidence for a relationship with low levels of both maternal education and SEP [102].…”
Section: Weaning/early-life Dietsupporting
confidence: 74%
“…Socio-economic differences in diet are well established; children from more deprived families have been found to consume more energy dense [35-38] and less nutrient-dense foods [39]. Factors such as availability, accessibility [40], parental education and income [37], and cost of foods have been identified as contributing factors [41].…”
Section: Discussionmentioning
confidence: 99%